2014
DOI: 10.1093/jxb/eru132
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic control of plant senescence and linked processes

Abstract: Senescence processes are part of the plant developmental programme. They involve reprogramming of gene expression and are under the control of a complex regulatory network closely linked to other developmental and stress-responsive pathways. Recent evidence indicates that leaf senescence is regulated via epigenetic mechanisms. In the present review, the epigenetic control of plant senescence is discussed in the broader context of environment-sensitive plant development. The review outlines the concept of epige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 131 publications
2
55
0
2
Order By: Relevance
“…Several lines of evidence indicate that leaf senescence is regulated by epigenetic mechanisms, such as histone modifications, chromatin architecture and DNA methylation (Fischer ; Humbeck ; Ay et al . ). It is proposed that unrepaired DNA damage increases not only mutations, but also heritable changes in DNA methylation (Holliday & Grigg ).…”
Section: Age‐associated Alterations Of Dna Methylation In Plantsmentioning
confidence: 97%
See 1 more Smart Citation
“…Several lines of evidence indicate that leaf senescence is regulated by epigenetic mechanisms, such as histone modifications, chromatin architecture and DNA methylation (Fischer ; Humbeck ; Ay et al . ). It is proposed that unrepaired DNA damage increases not only mutations, but also heritable changes in DNA methylation (Holliday & Grigg ).…”
Section: Age‐associated Alterations Of Dna Methylation In Plantsmentioning
confidence: 97%
“…It is possible that DNA methylation is an important mechanism for epigenetic regulation of plant ageing and senescence, since it is known that the major developmental phase transitions, plant stress responses and leaf senescence are under epigenetic control, including DNA methylation (Humbeck ; Ay et al . ). Therefore, in the present review we also aimed to summarise and discuss studies where levels of DNA methylation have been investigated in relation to plant chronological age or to the degree of maturity of plant tissues.…”
Section: Introductionmentioning
confidence: 97%
“…In addition to abiotic factors, attacks by pathogens are signaled to the chromatin to induce defensive gene expression [54,55]. Finally, intrinsic responses to wounding [56] or senescence [57] are able to modify chromatin configurations.…”
Section: Stress Types Modifying Chromatin Parametersmentioning
confidence: 99%
“…It was shown that SET domain-containing proteins regulated plant developmental processes such as floral organogenesis, seed development11 and plant senescence12. More recent studies demonstrated that SET domain-containing proteins were also involved in plant defense in response to different environmental stresses.…”
mentioning
confidence: 99%